RESEARCH OF THE CHEMICAL COMPOSITION OF PERFUMERY PRODUCTS - Karimova Dilovar Batirovna; SaidahmedovaNurxon Yusupovna; Mahmudov Ilhomjon Tolibjonovich (Journals Park Publishing, 2022)
A chromatographic study of 3 different samples of perfumes was identified as a result of gas chromatographic detectors and the content of their relative quantity. Depending on the type of product, the number of aromas is contained in the samples will differ. Samples 1 and 2 are studied from a combination with allergenic properties of linalal, lilial, α -izomethylionon and D-lemonen.
Keywords: perfumery, parfume, eau de parfum, eau de toilette, mass of selective detector.